Office laparoscopy under local anesthesia and conscious sedation - Saavedra, Jaime (Revista Colombiana de Obstetricia y Ginecología, 2000)
Laparoscopy under local anesthesia goes by the hand with laparoscopy's origin; at the beginning this was introduced as a procedure under local anesthesia because of the problems generated by the high costs of the procedure with general anesthesia. Micro laparoscopy under local anesthesia is one of the recent advances of the minimally invasive surgery, that combines two different techniques, the first one is the use of laparoscopes with a size less than 2mm., and the second one is the carrying out the laparosocopic procedure at different places from the operating theater. The laparoscopy under local anesthesia is used for diagnostic procedures and for simple operating theater procedures. The most important requirement for the success of a laparoscopy under local anesthesia is the patient's determination for taking the procedure under this technique.